Depressive Symptoms, Emotion Dysregulation, and Bulimic Symptoms in Youth With Type 1 Diabetes: Varying Interactions at Diagnosis and During Transition to Insulin Pump Therapy. (July 2016) - Young-Hyman, Deborah L.; Peterson, Claire M.; Fischer, Sarah; Markowitz, Jessica T.; Muir, Andrew B.; Laffel, Lori M.
This study evaluated the associations between depressive symptoms, emotion dysregulation and bulimic symptoms in youth with type 1 diabetes (T1D) in the context of the diagnosis and treatment of T1D. Study participants were 103 youth in 2 distinct groups: newly diagnosed (New) or transitioning to pump therapy (continuous subcutaneous insulin infusion [CSII]; "Pump"), who completed questionnaires regarding symptoms of depression, emotion dysregulation, and bulimia. Glycemic control (A1c), height, weight, and questionnaires were evaluated within 10 days of diagnosis (n = 58) or at education/clinic visit before starting insulin utilizing CSII (n = 45). In the newly diagnosed group, only depression accounted for significant variance in bulimia scores (β = .47, P < .01). For the group with disease treatment experience (Pump), but not for the newly diagnosed group (New), greater depressive symptoms and emotion dysregulation were associated with greater bulimic symptoms. Depressive symptoms and emotion dysregulation, an indicator of poor coping/behavioral control, could help explain adoption of disordered eating behaviors in youth with T1D who are transitioning to pump therapy.